Small-molecule inhibitors of P-Rex guanine-nucleotide exchange factors. (31st December 2022) - Lawson, CD; Hornigold, K; Pan, D; Niewczas, I; Andrews, S; Clark, J; Welch, HCE
ABSTRACT: P-Rex1 and P-Rex2 are guanine-nucleotide exchange factors (GEFs) that activate Rac small GTPases in response to the stimulation of G protein-coupled receptors and phosphoinositide 3-kinase. P-Rex Rac-GEFs regulate the morphology, adhesion and migration of various cell types, as well as reactive oxygen species production and cell cycle progression. P-Rex Rac-GEFs also have pathogenic roles in the initiation, progression or metastasis of several types of cancer. With one exception, all P-Rex functions are known or assumed to be mediated through their catalytic Rac-GEF activity. Thus, inhibitors of P-Rex Rac-GEF activity would be valuable research tools. We have generated a panel of small-molecule P-Rex inhibitors that target the interface between the catalytic DH domain of P-Rex Rac-GEFs and Rac. Our best-characterized compound, P-Rex inhibitor 1 (PREX-in1), blocks the Rac-GEF activity of full-length P-Rex1 and P-Rex2, and of their isolated catalytic domains, in vitro at low-micromolar concentration, without affecting the activities of several other Rho-GEFs. PREX-in1 blocks the P-Rex1 dependent spreading of PDGF-stimulated endothelial cells and the production of reactive oxygen species in fMLP-stimulated mouse neutrophils. Structure-function analysis revealed critical structural elements of PREX-in1, allowing us to develop derivatives with increased efficacy, the best with an IC50 of 2 µM. In summary, we have developed PREX-in1 and derivative small-molecule compounds that will be useful laboratory research tools for the study of P-Rex function. These compounds may also be a good starting point for the future development of more sophisticated drug-like inhibitors aimed at targeting P-Rex Rac-GEFs in cancer.